CLINICAL COMPARATIVE STUDY ON THE EFFICACY OF GHONTA PHALADI VARTI AND ARAGVADHADI VARTI IN THE MANAGEMENT OF NADI VRANA W.S.R. SINUS - Kumar Praveen, Prabudh; Savadi, *B.S. (International Journal of Ayurveda and Pharma Research, 2019)
Clinically Nadi Vrana forms if abscess is avoid or treated improperly and ineffectively with post-operative complications and complaints of recurrences in most of the cases by the line of treatment adopted by modern surgeons. In spite of tremendous progress in the field of modern surgery, still there or greatly analyzed chances of recurrence are noticed. Objectives: The study is aimed to know the comparative efficacy of Ghonta Phaladi Varti and Aragvadhadi Varti in the management of Nadi Vrana. Method: Total 30 patients diagnosed to be suffering from Nadi Vrana (Sinus) were selected randomly. These were divided into two groups A and B containing 15 patients in each. Group A patients were treated with Ghonta Phaladi Varti application and group B patients were treated with Aragvadhadi Varti application. Result: Comparative statistical analysis of both groups A Ghonta Phaladi Varti and B Aragvadhadi Varti denotes insignificant difference with respect to parameters such as length of the tract, discharge, surrounding skin, tenderness, temperature, pain, burning sensation and itching. But group A is more effective than group B. Interpretation: It is recommended to conduct clinical trial on large sample size may be with some acceptable modifications in drug, dose and durations which may give more beneficial result. Conclusion: When two groups were compared more improvement was seen in patients treated with Ghonta Phaladi Varti than Aragvadhadi Varti.